2020
DOI: 10.1038/s41598-020-68449-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of frontal prism structures and slope failures near the trench axis with shallow megathrust slip at the Japan Trench

Abstract: prism sediment, SU2 as incoming hemipelagic and pelagic soft sediment, SU3 as chert, and SU4 as igneous basement. We additionally interpreted a stratified unit TF, which shows a clear onlap relationship with SU2 at the trench axis, corresponding to the trench fill sediments (Fig. 2a,f). Three of the seismic profiles in Fig. 2c-e were acquired in the area with the huge shallow slip during the 2011 Tohoku earthquake around 38°-38°30′N. Seismic profiles HDMY069 and HD65B (Fig. 2c,d), where differential bathymetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 34 publications
(93 reference statements)
2
24
0
Order By: Relevance
“…An effective coefficient of basal friction of 0.09 represents a compressively critical state 27 of the plate boundary fault beneath the low-velocity wedge. This is consistent with the fold-and-thrust structures imaged within the sediments 30 and the reverse faults interpreted on the RTM section (Fig. 4 c).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…An effective coefficient of basal friction of 0.09 represents a compressively critical state 27 of the plate boundary fault beneath the low-velocity wedge. This is consistent with the fold-and-thrust structures imaged within the sediments 30 and the reverse faults interpreted on the RTM section (Fig. 4 c).…”
Section: Resultssupporting
confidence: 88%
“…1 ) to calculate the physical properties of the sediments. The spatial location of this line coincides with 2D seismic line MY101, which was acquired in 1999, and several studies 6 , 15 17 , 30 have been conducted to estimate the coseismic slip of 2011 Tohoku-Oki earthquake around this line. Previously, we used line D13 in a different study 42 to apply seismic full waveform inversion on the shallow sedimentary strata in the forearc upper slope.…”
Section: Methodsmentioning
confidence: 62%
“…However, deep-sea multibeam bathymetric surveys are generally supposed to map hundreds meter-scale seafloor morphological features for the purposes of marine geology and geophysics, therefore, very high accuracy measurements have rarely been required yet. The magnitudes of seafloor displacements become smaller in areas far away from the 2011 Tohoku-oki earthquake epicentral area (Fujiwara et al, 2017;Kodaira et al, 2020;Nakamura et al, 2020). In the case of the surveys to detect small seafloor displacements, the uncertainties in the bathymetric surveys are not negligible.…”
Section: Introductionmentioning
confidence: 99%
“…However, slip models constrained by other data and aftershocks (Nakamura et al., 2016), differential seafloor bathymetry (Kodaira et al., 2020), and near‐trench turbidities (Ikehara et al., 2016) (Figure 11) suggest that the main coseismic slip is limited to the south of 39.2°N. The higher‐frequency tsunami waves (Tappin et al., 2014) and seismic profiles of shallow structure (Nakamura et al., 2020) showed that gravitational slope failures of the trench inner wall may have substantially contributed to the proposed tsunami source around 39–40°N. Given the inherent uncertainties involved in the different types of observations, the northern reach of the rupture remains uncertain.…”
Section: The Features Of the Tohoku‐oki Earthquakementioning
confidence: 95%